DESIGN MODELING OF SAVONIUS-DARRIEUS TURBINE FOR SEA CURRENT ELECTRIC POWER PLANT - Boris Metheny; Rosyida Permatasari; Muhammad Sjahrul Annas (Universitas Mercu Buana, 2021)
Turbines convert the kinetic energy of ocean currents into electrical energy produced by the sea current electric power plant. This study aims to design a power generator turbine modeling that is carried out using the Computational Fluid Dynamic (CFD) approach by comparing the geometric performance based on the angle of attack and the Tip Speed Ratio (TSR) value of the Savonius-Darrieus Turbine. Having done several trials and errors during collecting the data, the value of the TSR 1.427; 2.853; 4.28; 5; and 5.7 is proposed. Here, the NACA 0018 series has been adopted on the current design of Savonius-Darrieus Turbine. The turbine has three blades, length of the span 357 mm, the diameter of turbine 428 mm, and length of the hydrofoil chord 40 mm. Effect of various angle of attacks from 0°up to 10° has been taken into account in the computational to obtain the coefficient power for each variation. The results revealed that the turbine with an angle of attack of 5°and TSR value of 5.0 has higher power coefficient value by 0.469 as compared with its angle of attack of 10°. It should be noted here that the increase of the angle of attack up to 10° resulted in a significant reduction of the power coefficient value of 0.206 as the value of TSR about 4.28. The addition of the Savonius Rotor results in increasing efficiency of the turbine for sea current applications.